Justice and empathy : toward a constitutional ideal - Burt, Robert A., 1939-2015; Iacobucci, Frank; Post, Robert, 1947- (New Haven : Yale University Press, 2017)
"An impassioned argument for the role of courts as a moral and social agent for change and protecting the vulnerable ... The Supreme Court long considered its highest mission to be the protection of individual liberty from intrusion by government, but the court shifted its focus to social and economic equality. Constitutional scholar Robert A. Burt explores this shift and its implications, especially for the legal protection of the vulnerable. Crucial to Burt's perspective is his unconventional view of the role of judges--not simply to decide disputes, but to promote a respectful dialogue leading to a genuine understanding between parties."--Publisher's website.
Foreword / by Robert C. Post -- Introduction / by Frank Iacobucci -- Part 1. Protecting vulnerable groups in principle. A living truth -- Judicial power to command -- All that is solid -- This word "reason" -- The healthiest possible soul -- The democratic path -- Part 2. Protecting vulnerable groups in practice. Enslaving criminals -- Respecting same-sex relations -- Abortion : private and public considerations -- Race relations : between emancipation and subjugation -- Ordering moral deliberations.
Includes bibliographical references (pages 185-202) and index.
Keywords: United States. -- Supreme Court; United States. -- Supreme Court; Judicial power -- United States; Constitutional law -- Social aspects -- United States; Political questions and judicial power -- United States; Sociological jurisprudence; Constitutional law -- Social aspects; Judicial power; Political questions and judicial power; Sociological jurisprudence; United States